DETERMINAN RETURN SAHAM SEKTOR PROPERTI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Maulida Armanusa Ramadhafani (2023)
This study aims to analyze the influence of micro factors originating from internal companies consisting of Return on Equity (ROE) and Earning Per Share (EPS) as well as macro factors originating from external companies, namely macroeconomic factors consisting of economic growth, interest rates, and world oil prices on stock returns of property sector companies listed on the Indonesia Stock Exchange (IDX). The purposive sampling method was used to determine the sample in this study with the period 2012 - 2021 and the data used was secondary data. The hypothesis test applied in this study is the panel data regression analysis technique with the Stata 17 program and the significance level used is 5%. Simultaneously, the results of the hypothesis test reveal that the five independent variables together have a significant effect on the stock returns of property sector companies listed on the IDX. Partially, ROE and world oil prices have a significant effect on stock returns of property sector companies listed on the IDX, while EPS, economic growth, and interest rates have no effect on stock returns of property sector companies listed on the IDX.